Implikasi Pandangan Filsafat Pragmatisme John Dewey Terhadap Praktik Pendidikan Serta Relevansinya Dengan Merdeka Belajar Kampus Merdeka - Ega Nasrudin; Shalza Alifia Yasha; Udin Supriadi (Jurnal Kajian Ilmiah, 2025)
This study examines the implications of John Dewey's pragmatism philosophy views on educational practice along with its relevance to Merdeka Learning Merdeka Campus. A qualitative approach of literature study type is used in this research. The results of this study found that the involvement of students in participating in one of the programs offered and the process of training problem-solving skills in each form of the program make MBKM can be seen as pragmatic education. John Dewey's pragmatism education philosophy views education as a process of familiarizing individuals in overcoming every problem in their environment. Education should encourage students to have the skills to overcome existing problems. Apart from that, this research also describes how the implications of John Dewey's pragmatism education concept in educational practice. For students, they need to have useful skills by getting used to implementing learning using collaborative and interdisciplinary approaches in solving problems. For teachers, they need to apply the right learning approach method. The learning approach that is considered appropriate must have collaborative characteristics, emphasize interdisciplinary approaches, and train students in problem solving. For schools or policy makers, schools and or policy making institutions need to ensure that the curriculum implemented has encouraged students to get used to being actively involved in problem solving. The curriculum in this case presents situations where learners are directed to practice solving existing problems.